Projeto de observadores de estado utilizando algoritmo genético - Oliveira, Clayton Antonio de Miranda (Universidade Federal Rural do Semi-Árido, 2014)
In this paper, we propose an appropriate genetic algorithm to design state observers for multivariable control systems, which response time meets the specifications previously provided by the user of the system, in terms of the maximum overshoot, and in terms of the settling time. For this, will be designed and evaluated different forms of initialization and different forms of setup the genetic algorithm. Furthermore, we intend to investigate the performance results of this technique in control systems utilizing state observers full order or reduced order. Through this analysis, intend to contribute to the specification of an appropriate genetic algorithm to design state observers for multivariable control systems, by making this an efficient alternative to traditional methods in the literature
State observer design using genetic algorithm
Keywords: Multivariable Control Systems; State Observers; Genetic Algorithms; Transient Response; Sistemas de Controle Multivariáveis; Observadores de Estado; Algoritmos Genéticos; Resposta Transitória; ENGENHARIAS::ENGENHARIA ELETRICA